Testing the CAPM and Three Factors Model in China: Evidence from the Shanghai Stock Exchange - Wang, Weixi (2015)
Since inception, China’s stock market has grown rapidly and has become one of the most important emerging markets in the world. However, many popular financial media depicts China’s stock market as irrational. Besides, empirical studies on asset pricing in China’s stock market do not provide a consistent conclusion for different periods. This study tests the Capital Asset Pricing Model (CAPM) and Fama-French Three Factors Model in Shanghai Stock Exchange, China. For validity test of the CAPM, I follow the Fama-MacBeth (1973) procedure on a data set consisting of 180 A-shares with daily frequencies. Considerable evidence is obtained to conclude that the CAPM is not suitable to predict stock returns in China’s stock market. Beta alone cannot solely measure the risk and the stock return is not linear related to it. For validity test of Three Factors Model, I employ the Fama-French (1993) procedure to examine whether the size and book-to-market effect exists in China. Empirical results confirm the “small firm effect” but challenge Fama and French (1996) who states value firm outperform the growth firm. Besides, the results provide evidence that Three Factors Model have a better explanatory power than the CAPM. The findings suggest that mean-variance efficient investors can form their portfolio with small and low book-to-market equity firms to achieve higher risk-adjusted returns.